Improving Driver Warnings Accuracy Using Low Cost Sensors - Alla Srija, C.Chandrima, Bajarang, Mamatha.K.R, Poornima.L (International Journal of Advanced Science and Technology, 2020)
The project uses the concept of LI-FI technology, how two vehicles are communicated with the help of LED bulbs as a transmitter and receiver circuit. By implementing this technology, we can minimize the road accidents and many human lives can be saved. We use a device called as Ultrasonic sensor to measure the distance and to communicate between the two vehicles when they come in contact at some range that is preferred for the sensor. Using LIFI technology data is being transmitted from one vehicle to another and the data can be any data like audio, video or text. In order to implement a low cost and higher efficiency system we are adopting this concept. In present world, the usage of LED lights for illumination is drastically increasing because of its benefits like fast switching, high power efficiency and safe to human vision. Henceforth, this project offers eco-friendly data communication system over evident light which resides white LEDs that transmit audio signals to the receiver that contains solar panel that is associated to both the amplifier and speakers that recovers back the inventive signal by amplifying.